Effect of perioperative intravenous lidocaine on postoperative outcomes in patients undergoing resection of colorectal cancer: a protocol for systematic review and meta-analysis - Lulong Bo; Wentao JI; Xiaoting Zhang; Guolin Sun; Xiandong Wang; Jinjun Bian (BMJ Open)
Introduction Techniques using local anaesthetics provide high-quality analgesia, while the anti-inflammatory properties of these drugs may represent an additional advantage. Perioperative intravenous lidocaine has shown positive effects not only on postoperative pain but also on bowel function and duration of hospital stay, due to its analgesic, anti-inflammatory and opioid-sparing effects. However, these potential benefits are not well established in patients undergoing resection with colorectal cancer. This research aims to determine the effect of perioperative intravenous lidocaine on postoperative outcomes in patients undergoing resection of colorectal cancer.Methods and analysis PubMed, Embase, Web of Science, CNKI, SinoMed and WanFang Data databases were electronically retrieved to include the randomised controlled trials comparing perioperative intravenous lidocaine with placebo infusion in patients undergoing resection of colorectal cancer before August 2021. Registers of clinical trials, potential grey literature and abstracts from conferences will also be searched. Two reviewers will screen literature, extract data and assess risk of bias of studies included independently. The primary outcome variable will be long-term survival outcome, tumour recurrence and metastasis rate, and restoration of intestinal function. The secondary outcome variables will consist of the severity of postoperative pain at 4, 12, 24 and 48 hours after surgery, the incidence of postoperative nausea and vomiting, and the length of hospital stay. A meta-analysis will be performed using RevMan V.5.4 software provided by the Cochrane Collaboration and Stata V.12.0. subgroup and sensitivity analyses will be conducted.Ethics and dissemination Because the data used for this systematic review will be exclusively extracted from published studies, ethical approval and informed consent of patients will not be required. The systematic review will be published in a peer-reviewed journal, presented at conferences and shared on social media platforms.PROSPERO registration number CRD42020216232.